Conflict in Roles: Lying to the In-Group Versus the Out-Group in Negotiations. (May 2014) - Glac, Katherina; Warren, Danielle E.; Chen, Chao C.
This empirical study examines how group membership affects the likelihood of lies occurring in a two-person negotiation setting involving an experimental design with a repeated ultimatum bargaining. To better understand the reasoning of the negotiator in in-group and out-group bargaining exercises, the authors also examined perceptions of fairness in relation to offers for the in-group and out-group. The authors find that when negotiating, individuals tell lies of greater magnitude to out-group members than to in-group members. In both situations, the magnitude of the initial lie predicts the likelihood that a concealment lie (i.e., another lie to conceal the initial lie) will be told. The study also finds that in negotiations with in-group members, the relationship between the initial lie and the concealment lie is moderated by the negotiator's perceptions of unfair treatment toward the in-group bargaining partner. The authors assert that concealment lies with in-group members allow the individual to appear to maintain both the roles of a self-interested negotiator and a fair group member. The authors tested three hypotheses using a natural group of 42 undergraduate students who belonged to a sports team at a large Northeastern university. Implications for stakeholder research are addressed.